Pengaruh Mutu Pelayanan Kesehatan Terhadap Kepuasan Pasien Rawat Jalan di RSU UKI Jakarta Timur 2022 - Sry Indah Meilani Lumban Gaol; Lia Idealistiana (Universitas Aisyah Pringsewu (UAP) Lampung, 2022)
The quality of health services as an indicator of the quality of health services is one of the determining factors for the image of health service institutions in the eyes of the community. This happens because it is a professional group with the highest number, at the forefront and closest to patients and their families. One indicator of the quality of health services is whether the health services provided are satisfactory or not. Satisfaction is a comparison between the quality of services obtained with the desires, needs, and expectations. This study aims to determine the effect of the quality of health services on the satisfaction of outpatients at RSU UKI. and whether there is an influence between the physical appearance of the nurse/midwife, reliability, responsiveness, assurance, and empathy for patient satisfaction. This research used descriptive method with cross sectional approach, sampling technique and total sampling consisted of 86 respondents. The results showed that there was an effect of service on patient satisfaction (p-value = 0.001). there is an influence between the appearance of health services on patient satisfaction (p-value = 0.001 less than 0.05). there is an influence between the reliability of health services on patient satisfaction (p-value = 0.000 less than 0.05), there is an influence between the responsiveness of health services to patient satisfaction (p-value = 0.000 less than 0.05), there is an influence between health care insurance and patient satisfaction ( p-value = 0.000 less than 0.05), there is an effect of empathy for health services on patient satisfaction (p-value = 0.000 less than 0.05). It is recommended that nurses/midwives continue to develop knowledge about the quality of health services so that each nurse/midwife can maximize the best service. Abstrack: Mutu pelayanan kesehatan sebagai indikator mutu pelayanan kesehatan yang terjadi salah satu faktor penentu citra institusi pelayanan kesehatan dimata masyarakat. Hal ini terjadi karena merupakan kelompok profesi dengan jumlah terbanyak, paling depan dan terdekat dengan pasien dan keluarganya. Salah satu indikator dari mutu pelayanan kesehatan itu adalah apakah pelayanan kesehatan yang diberikan itu memuaskan atau tidak. Kepuasan merupakan perbandingan antara kualitas jasa pelayanan yang didapat dengan keinginan, kebutuhan, dan harapan. Penelitian ini bertujuan untuk mengetahui pengaruh mutu pelayanan kesehatan terhadap kepuasan pasien rawat jalan RSU UKI, dan ada tidaknya pengaruh antara wujud/tampilan fisik perawat/bidan, kehandalan, ketanggapan, jaminan, dan empati terhadap kepuasan pasien. Penelitian ini menggunakan metode deskriptif dengan pendekatan cross sectional, teknik pengambilan sampel dan total sampling terdiri dari 86 responden. Hasil penelitian menunjukkan adanya pengaruh pelayanan terhadap kepuasan pasien (p-value=0,001). Adanya pengaruh antara wujud/tampilan pelayanan kesehatan terhadap kepuasan pasien (p-value=0,001 kurang dari 0.05). adanya pengaruh antara kehandalan pelayanan kesehatan terhadap kepuasan pasien (p-value=0,000 kurang dari 0.05), adanya pengaruh antara ketanggapan pelayanan kesehatan terhadap kepuasan pasien (p-value=0,000 kurang dari 0,05), adanya pengaruh antara jaminan pelayanan kesehatan terhadap kepuasan pasien (p-value=0,000 kurang dari 0,05), adanya pengaruh antara rasa empati pelayanan kesehatan terhadap kepuasan pasien (p-value=0,000 kurang dari 0,05). Disaranankan perawat/bidan untuk terus mengembangkan ilmu tentang mutu pelayanan kesehatan supaya setiap perawat/bidan dapat memaksimalkan pelayanan yang terbaik.